Dalitz plot analysis of D+s→K+K−π+ - Amo Sanchez, Pablo del; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We perform a Dalitz plot analysis of about 100 000 D+s decays to K+K−π+ and measure the complex amplitudes of the intermediate resonances which contribute to this decay mode. We also measure the relative branching fractions of D+s→K+K+π− and D+s→K+K+K−. For this analysis we use a 384 fb−1 data sample, recorded by the BABAR detector at the PEP-II asymmetric-energy e+e− collider running at center-of-mass energies near 10.58 GeV.